Imagens na imensidão: os iconotextos e o indizível em A imensidão íntima dos carneiros, de Marcelo Maluf - Gabriela Maria Hollanda Ferreira de Farias (2023)
The present work aims to investigate the existing iconotexts in the self-fabulative novel A imensidão intimate dos carneiros (2019) [The intimate imensity of sheep] by Marcelo Maluf, seeking to understand to what extent the unspeakable inhabits the images within the narrative. The contemporary Brazilian author of Syrian-Lebanese descent dedicated himself to narrating his family's history from the fragmented perspectives of the homonymous characters Marcelo and Assaad, grandson and grandfather, facing the trauma of war and immigration. The intermedial aspects of this novel are remarkable. Within this fragmented narrative are descriptions or ekphrases of paintings, photographs and dances that were analyzed, taking into account their historical and spatial contexts, in order to understand what their functions were (BERTHO, 2014) for narrative construction. The iconotexts (LOUVEL, 2006, 2012) identified are of two types: images in absentia and in praesentia. We conclude that, among the existing iconotexts, the painting of the Holy Supper has greater prominence within the novel, having the function of structuring the narrative, in addition to characterizing the characters, especially with regard to the pictorial character Judas Iscariot, which is related both to the character literary Marcelo and with the author Marcelo Maluf himself. To do so, we use as a qualitative theoretical basis, in addition to the author's critical fortune: the concept of self-fabulation by COLONNA (2014) and the historical context of the Lebanese heritage pointed out by TRUZZI(2009, 2019) and GATTAZ (2012); the notion of unspeakability by ARROUYE (2011) and SELIGMANNSILVA (2003, 2008, 2010); as functions of BERTHO (2014); LOUVEL's notion of iconotext (2006, 2012); the differential model by ROBILLARD (1998) and one of the concepts of ekphrasis byCLÜVER (1997); and, regarding the photographs, the authors BARTHES (1984) and KOSSOY(1998, 2001, 2007).